ANALISIS DAN PENGEMBANGAN SISTEM INFORMASI RAPOR ONLINE BERBASIS WEB DAN MOBILE PADA SMA NEGERI 1 GEDONG TATAAN - Aristoteles Aristoteles; Widiarti Widiarti; Rizki Agung Permana (Jurnal Komputasi, 2013)
Online school report card information system based on web and mobile is an information system that can give us information service with student academic data form that we can access it through web and mobile. This online school report card information system based on web and mobile is a development form from online school report card information system by Giska Putri Wulandari that existed previously.Research and development purposes of online school report card information system are for give ease at student and teacher data processing, simplify in student academic data processing and delivery the information to pupil through network mobile and to detect how much influence of online school report card information system based on web and mobile towards system user satisfaction level.Research method that used in this research is based on field research method. And the development system is uses waterfall model. Software that used: windows xp professional, macromedia dream weaver 8,Â  and xampp 1.6.8.Result from this Research and development of online school report card information system is conclusion from questionnaire data and a application web named: online school report card information system based on web and mobile on SMA Negeri 1 Gedong Tataan.Keywords: Analysis information system, online report, web and mobile